Coulomb branch of N=4 SYM and dilatonic scions in supergravity - Maurizio Piai (Physical Review D, 2021)
We find a parametrically light dilaton in special confining theories in three dimensions. Their duals form what we call a scion of solutions to the supergravity associated with the large-N limit of the Coulomb branch of the N = 4 Super-Yang-Mills (SYM) theory. The supergravity description contains one scalar with bulk mass that saturates the Breitenlohner-Freedman unitarity bound. The new solutions are defined within supergravity, they break supersymmetry and scale invariance, and one dimension is compactified on a shrinking circle, yet they are completely regular. An approximate dilaton appears in the spectrum of background fluctuations (or composite states in the confining theory), and becomes parametrically light along a metastable portion of the scion of new supergravity solutions, in close proximity of a tachyonic instability. A first-order phase transition separates stable backgrounds, for which the approximate dilaton is not parametrically light, from metastable and unstable backgrounds, for which the dilaton becomes parametrically light, and eventually tachyonic.